The Influence Of Product Innovation And Digital Marketing On The Competitiveness Of Msmes In Bengkulu City - Andini, Puja; Nasution, Suswati; Fitriano , Yun (Jurnal Ekonomi Islam, Akuntansi, dan Manajemen, 2025)
Micro, Small, and Medium Enterprises (MSME) play a central role in the Indonesian economy. The growth of MSME has resulted in intense competition. Therefore, appropriate strategies are needed to remain competitive. This study aims to empirically examine the influence of product innovation and digital marketing on the competitiveness of MSME in Bengkulu City.This study used a quantitative method using purposive sampling. A sample of 30 respondents, micro MSME entrepreneurs in the Anggut area of Bengkulu City, was selected. Data were obtained from questionnaires distributed directly using a QR code Google Form using a Likert scale. Data analysis used multiple linear regression analysis using SPSS version 26.There is an influence of product innovation (X1) on the competitiveness (Y) of Micro MSMEs in the Anggut area of Bengkulu City with a sig value of 0.000 <0.05 and t count> t table (3.753>2.05183) thus Ho is rejected and Ha is accepted. From the significance value obtained that variable X has an effect on competitiveness (Y). There is digital marketing (X2) on the competitiveness (Y) of micro MSMEs in the Angguk area of Bengkulu City with a sig value of 0.002 <0.05 and t count> t table (3.528>2.05183) thus Ho is rejected and Ha is accepted. From the significance value obtained that variable X2 has an effect on competitiveness (Y). Product innovation and digital marketing jointly influence competitiveness, with a Fsig value <α, where Fsig is 0.000 and the calculated F value is 270.064 > Ftable 3.35.